Development of Landslide Sentry Prototype with IoT Monitoring System - binti Marhalim, Seri Najihah; Afishah Alias (Enhanced Knowledge in Sciences and Technology, 2024)
An IoT Landslide Sentry system has been developed to address the critical need for real-time landslide risk assessment in geohazard-prone areas. The system integrates advanced sensors, including soil moisture, ultrasonic distance, and vibration sensors, with the ESP32 microcontroller. Through extensive calibration testing, the accuracy of each sensor has been validated, with minimal average percentage errors recorded. The project further explores the Blynk dashboard outcomes, showcasing the system’s responsiveness to varying soil conditions and potential landslide risk factors. The study aims to provide a comprehensive solution for geohazard monitoring, contributing to proactive risk management in landslide-prone regions.